(untitled) (International Journal on Stereo & Immersive Media, 2017)
SHIFTING TEMPORAL PLANES: AFFECTIVE TEMPORALITY IN IMMERSIVE AUDIOPHOTOGRAPHIC INSTALLATION ART HALI SANTAMAS - Independent researcher, UK